Polishing composition with excellent storage stability and method for producing the same

CN121285611BActive Publication Date: 2026-10-09NISSAN CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202480038208.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-05-27
Filing Date
2024-09-27
Publication Date
2026-10-09
Estimated Expiration
2044-09-27

AI Technical Summary

Benefits of technology

[0060] In this invention, by highly controlling the affinity between the silica particles used as abrasive grains and the aqueous medium in the abrasive composition, especially in silicon wafer abrasives, it is possible to simultaneously improve the abrasive speed and the storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

Provided is a polishing composition that can be used for polishing of silicon wafers, achieves a high polishing rate, and improves storage stability. A polishing composition is a polishing composition comprising a water dispersion of silica particles, and has an Rsp value of 0.01 or greater but less than 0.15, derived from the relaxation time of the water dispersion of silica particles and pure water as measured by pulsed NMR, Rsp = (Rav - Rb) / (Rb). Rsp is an index indicating the affinity of silica particles for water, Rav is the inverse of the relaxation time of a water dispersion of silica particles having a silica concentration of 5% by mass, and Rb is the inverse of the relaxation time of pure water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a grinding composition using silica-based abrasive grains and a method for manufacturing the same. Background Technology

[0002] Polishing compositions using silica-based abrasive grains are used for polishing silicon wafers. These compositions typically contain silica-based abrasive grains in an aqueous medium such as water, and may optionally contain alkaline compounds, water-soluble compounds, chelating agents, oxidizing agents, metal corrosion inhibitors, etc.

[0003] To shorten the grinding time based on high grinding speeds, a grinding composition defined using a function representing affinity for water has been disclosed, the function being derived from the relationship between the reciprocal of the relaxation time of pulsed NMR of silica abrasive grains in a dispersed state and the total surface area of ​​the silica abrasive grains (see Patent Document 1).

[0004] In addition, a grinding composition that defines the relationship between the BET specific surface area of ​​silica particles contained as abrasive grains and the specific surface area based on pulse NMR method has been disclosed (see Patent Document 2).

[0005] Furthermore, a grinding composition for evaluating NMR relaxation time using the solvent affinity of abrasive particles has been disclosed (see Patent Documents 3 and 4).

[0006] A grinding composition was previously disclosed in which the pulse NMR measurement value of the dispersion of silica particles, Rsp = (Rav-Rb) / (Rb), is 0.15 to 0.7, and the shape factor SF1 of the silica particles, SF1 = (area of ​​a circle with the maximum diameter of the particles as the diameter) / (projected area), is 1.20 to 1.80, thereby increasing the grinding speed and improving the grinding surface (see Patent Document 5).

[0007] [Existing Technical Documents]

[0008] [Patent Literature]

[0009] [Patent Document 1] International Publication No. 2018 / 116890

[0010] [Patent Document 2] International Publication No. 2015 / 152151

[0011] [Patent Document 3] Japanese Patent Application Publication No. 2017-117894

[0012] [Patent Document 4] International Publication No. 2018 / 012174

[0013] [Patent Document 5] International Publication No. 2020 / 091000 Summary of the Invention

[0014] The objective of this invention is to provide a polishing composition that achieves high polishing speed when used for polishing silicon wafers and improves storage stability during storage or transport.

[0015] The inventors focused on the amount of water molecules confined to the surface of silica particles, using the Rsp value derived from the relaxation time obtained by pulse NMR measurement as an indicator. They discovered that by using silica particles with Rsp values ​​within a specified range as abrasives, high grinding performance can be maintained, and the storage stability of the grinding composition becomes good.

[0016] The invention of this application, as a first aspect, is a grinding composition comprising an aqueous dispersion of silica particles, wherein the Rsp value derived from the relaxation time of the aqueous dispersion of silica particles and pure water by pulse NMR measurement is 0.01 or more and less than 0.15.

[0017] Rsp = (Rav - Rb) / (Rb)

[0018] Where Rav is the reciprocal of the relaxation time of an aqueous dispersion of silica particles with a silica concentration of 5% by mass, and Rb is the reciprocal of the relaxation time of pure water.

[0019] As a second point of view, according to the grinding composition described in the first point of view, the silica particles contained in the silica particle aqueous dispersion have an average secondary particle size of 40-200 nm as determined by dynamic light scattering and an average primary particle size of 20-100 nm as determined by nitrogen adsorption.

[0020] As a third point of view, according to the grinding composition described in the first point of view, for silica particle powder, the amount of silanol groups, calculated by the following formula based on the mass loss when heated from room temperature to 700°C in thermogravimetric analysis and the molecular weight of water molecules, is 0.1~1.5 mmol / g. The silica particle powder is obtained by freezing a treatment solution at a temperature of -70°C to -80°C, and then freeze-drying it at room temperature under a pressure below 5 Pa to remove the dispersion medium. The treatment solution is obtained by sequentially contacting the silica particle aqueous dispersion with a cation exchange resin, an anion exchange resin, and a cation exchange resin to perform ion exchange.

[0021] Silanol group content (mmol / g) = 2 × (M2 - M1) ÷ M H2O ÷ (M0-M1)×1000

[0022] Where M0 represents the mass of silica powder used for the heating weight analysis before heating, M1 represents the mass reduction at the time point of reaching 200℃, and M2 represents the mass reduction at the time point of reaching 700℃. H2O This indicates the molecular weight of a water molecule.

[0023] As a fourth point of view, according to the grinding composition described in the first point of view, the density of the silica particle powder, as determined by dry density measurement, is 2.20~2.35 g / cm³. 3 The silica particle powder is obtained by freezing the treatment liquid at a temperature of -70℃ to -80℃, and then freezing and drying it at room temperature under a pressure of less than 5Pa to remove the dispersion medium. The treatment liquid is obtained by sequentially contacting the silica particle aqueous dispersion with a cation exchange resin, anion exchange resin and cation exchange resin to perform ion exchange.

[0024] As a fifth point of view, based on the grinding composition described in the first point of view, for silica particle powder, the specific surface area (S) based on the water vapor adsorption method... H2O ) relative to the specific surface area (S) based on nitrogen adsorption method N2 The ratio of (S) H2O / S N2 The silica particle powder is 0.10~0.65. It is obtained by heating the treatment liquid at 140°C for 2 hours and then at 290°C for 1 hour to remove the dispersion medium. The treatment liquid is obtained by contacting the silica particle aqueous dispersion with cation exchange resin, anion exchange resin and cation exchange resin in sequence to perform ion exchange.

[0025] As a sixth point of view, in the grinding composition according to any one of the first to fourth points of view, the silica particle aqueous dispersion is a dispersion that has undergone a thermal process at a temperature of 140°C or higher and less than 260°C.

[0026] As a seventh point of view, in the grinding composition according to any one of the first to fifth points of view, the concentration of the silica particles is 1 to 40 by mass.

[0027] As an eighth point of view, the grinding composition according to any one of the first to seventh points of view further comprises at least one additive selected from acidic compounds, basic compounds, water-soluble compounds, chelating agents, oxidizing agents and metal corrosion inhibitors.

[0028] As a ninth point of view, in the grinding composition according to the eighth point of view, the alkaline compound is at least one alkaline compound selected from alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonates, and nitrogen-containing alkaline compounds.

[0029] As a tenth point of view, in the grinding composition according to the eighth point of view, the chelating agent is an aminocarboxylic acid chelating agent or a phosphonic acid chelating agent.

[0030] As the 11th point of view, the grinding composition according to any one of the 1st to 10th points of view has a pH value of 1 to 12.

[0031] As a 12th point of view, in a test in which the grinding composition is heated and stored at 50°C for 28 days, the increase rate of the average secondary particle size of the grinding composition after being heated and stored at 50°C for 28 days, as measured by dynamic light scattering, is less than 5%, relative to the average secondary particle size of the grinding composition before being heated and stored at 50°C for 28 days.

[0032] As a 13th point of view, the polishing composition according to any one of the 1st to 12th points of view is a composition for polishing silicon wafers or device wafers.

[0033] As the 14th point, a method for manufacturing a grinding composition according to any one of the 1st to 13th points comprises:

[0034] The process of preparing a colloidal silica dispersion as a precursor; and

[0035] The process of obtaining the silica particle aqueous dispersion by heating the precursor at a temperature above 140°C and below 260°C.

[0036] The 15th point is a silica particle dispersion, which is a silica particle dispersion containing a solvent and silica particles, wherein the Rsp value derived from the relaxation time of the silica particle dispersion and a blank solution by pulse NMR measurement is 0.01 or higher and less than 0.15.

[0037] Rsp = (Rav - Rb) / (Rb)

[0038] Where Rav is the reciprocal of the relaxation time of a silica particle dispersion with a silica concentration of 5% by mass, and Rb is the reciprocal of the relaxation time of the blank solution.

[0039] As a sixth point of view, in the silica particle dispersion described in the fifth point of view, the solvent comprises water.

[0040] As the 17th point of view, according to the silica particle dispersion described in the 15th point of view, the average secondary particle size of the silica particles, as determined by dynamic light scattering, is 40~200nm, and the average primary particle size, as determined by nitrogen adsorption, is 20~100nm.

[0041] As the 18th point of view, according to the silica particle dispersion described in the 15th point of view, for silica particle powder, the amount of silanol groups, calculated by the following formula from the mass loss when heated from room temperature to 700°C in thermogravimetric analysis and the molecular weight of water molecules, is 0.1~1.5 mmol / g. The silica particle powder is obtained by freezing the treatment solution at a temperature of -70°C to -80°C, and then freeze-drying it at room temperature under a pressure below 5 Pa to remove the dispersion medium. The treatment solution is obtained by sequentially contacting the silica particle dispersion with a cation exchange resin, an anion exchange resin, and another cation exchange resin to perform ion exchange.

[0042] Silanol group content (mmol / g) = 2 × (M2 - M1) ÷ M H2O ÷ (M0-M1)×1000

[0043] Where M0 represents the mass of silica powder used for the heating weight analysis before heating, M1 represents the mass reduction at the time point of reaching 200℃, and M2 represents the mass reduction at the time point of reaching 700℃. H2O This indicates the molecular weight of a water molecule.

[0044] As the 19th point of view, according to the silica particle dispersion described in the 15th point of view, the density of the silica particle powder, as determined by dry density measurement, is 2.20~2.35 g / cm³. 3 The silica particle powder is obtained by freezing the treatment liquid at a temperature of -70℃ to -80℃, and then freezing and drying it at room temperature under a pressure of less than 5Pa to remove the dispersion medium. The treatment liquid is obtained by sequentially contacting the silica particle dispersion with a cation exchange resin, anion exchange resin and cation exchange resin to perform ion exchange.

[0045] As the 20th point of view, based on the silica particle dispersion described in the 15th point of view, for silica particle powder, the specific surface area (S) based on the water vapor adsorption method... H2O ) relative to the specific surface area (S) based on nitrogen adsorption method N2 The ratio of (S) H2O / S N2The silica particle powder is 0.10~0.65. It is obtained by heating the treatment liquid at 140°C for 2 hours and then at 290°C for 1 hour to remove the dispersion medium. The treatment liquid is obtained by contacting the silica particle dispersion with cation exchange resin, anion exchange resin and cation exchange resin in sequence to perform ion exchange.

[0046] As the 21st point of view, the silica particle dispersion according to any one of the 15th to 20th points of view is a dispersion that has undergone a thermal process at a temperature of 140°C or higher and less than 260°C.

[0047] As the 22nd point of view, in the silica particle dispersion according to any one of the 15th to 20th points of view, the concentration of the silica particles is 1 to 40 by mass.

[0048] As the 23rd point, a method for manufacturing a silica particle dispersion according to any one of the 15th to 22nd points is provided, comprising:

[0049] The process of preparing a colloidal silica dispersion as a precursor; and

[0050] The process of obtaining the silica particle dispersion by heating the precursor at a temperature above 140°C and below 260°C.

[0051] This invention relates to silica particles for abrasives, focusing on the amount of water molecules confined to the surface of silica particles as an indicator, using the Rsp value derived from the relaxation time of a dispersion obtained by dispersing it in an aqueous medium for a grinding composition and pure water by pulse NMR measurement. It has been found that by setting a specific Rsp value, high grinding speeds can be achieved and the storage stability of the grinding composition can be improved.

[0052] High grinding speeds lead to increased wafer production efficiency, thus requiring grinding compositions to achieve high grinding speeds. Furthermore, if the silica particles in the grinding composition have poor storage stability, they can agglomerate and form tiny foreign objects during storage or transport. These foreign objects become a major cause of reduced grinding speeds and increased defects during grinding, thus requiring high storage stability as well.

[0053] The grinding composition contains silica particles as abrasive grains. Depending on their surface state, the interaction between the silica particles and the aqueous medium in the grinding composition changes, and this change in interaction affects the grinding speed and storage stability of the grinding composition.

[0054] In the silica particles used as abrasive grains in abrasive compositions, the water present on and around the particle surface is classified into bound water and free water according to its state. Free water refers to water that exists freely around the silica particles but does not interact with them. On the other hand, bound water refers to water that is hydrogen-bonded to the silica particles through silanol groups on the surface of the silica particles. This bound water plays an important role in ensuring good contact between the silica particles and the water.

[0055] The state (behavior) of water molecules can be determined from the relaxation time of the protons in water molecules, which is obtained by pulse NMR measurement.

[0056] Regarding the relaxation mechanism in nuclear magnetic resonance (NMR), there is a process of releasing absorbed energy and a process in which the phase of uniform nuclear spin precession becomes disordered. The former is called spin-lattice relaxation (longitudinal relaxation), and its relaxation time is called T1. The latter is called spin-spin relaxation (transverse relaxation), and its relaxation time is called T2.

[0057] In T1 relaxation, relaxation is most likely to occur when the velocity of molecular motion is equal to the resonant frequency. For example, free water molecules that are not in contact with silica particles (free water) and water molecules that are in contact with silica particles (bound water) have different response times, i.e., relaxation times, to changes in a magnetic field. In this case, a shorter relaxation time is considered to indicate that the particles in contact with water have a larger surface area and higher particle dispersion.

[0058] Furthermore, relaxation occurs during T2 relaxation through magnetic interactions. The determination of relaxation time based on pulsed NMR can be considered a method utilizing the difference in T2 relaxation.

[0059] The presence of this bound water within a specific range effectively influences grinding speed and storage stability during grinding.

[0060] In this invention, by highly controlling the affinity between the silica particles used as abrasive grains and the aqueous medium in the abrasive composition, especially in silicon wafer abrasives, it is possible to simultaneously improve the abrasive speed and the storage stability. Detailed Implementation

[0061] The present invention will now be described in detail. Furthermore, in the present invention, the silica particle dispersion is a dispersion in which silica particles are dispersed in water or an organic solvent, or a mixture of water and an organic solvent. Sometimes, the aqueous dispersion of silica particles dispersed in water, the organic solvent dispersion of silica particles dispersed in an organic solvent, and the mixed solvent dispersion of silica particles dispersed in a mixture of water and an organic solvent are referred to as colloidal silica dispersion or silica sol, and the silica particles are referred to as colloidal silica (colloidal silica).

[0062] <Rsp value>

[0063] The present invention relates to a grinding composition comprising an aqueous dispersion of silica particles, wherein the Rsp value derived from the relaxation time of the aqueous dispersion of silica particles and pure water by pulse NMR is 0.01 or more and less than 0.15. The present invention also relates to a silica particle dispersion comprising a solvent and silica particles, wherein the Rsp value derived from the relaxation time of the silica particle dispersion and a solvent (e.g., pure water) by pulse NMR is 0.01 or more and less than 0.15.

[0064] Rsp = (Rav - Rb) / (Rb)

[0065] The Rsp value is an indicator of the affinity of silica particles for solvents, especially for water molecules. Rav is the reciprocal of the relaxation time of a silica particle dispersion with a silica concentration of 5% by mass (e.g., an aqueous silica particle dispersion), and Rb is the reciprocal of the relaxation time of the solvent (e.g., pure water).

[0066] The Rsp value can be set to, for example, 0.03 or higher and less than 0.15, 0.05 or higher and less than 0.15, 0.01 to 0.14, 0.03 to 0.14, 0.05 to 0.14, or 0.07 to 0.14.

[0067] With an Rsp value of 0.01 or higher, silica particles exhibit moderate water affinity, thus maintaining dispersibility in solvents or grinding compositions. Furthermore, with an Rsp value less than 0.15, the hydroxyl groups (OH groups) of water molecules confined near the surface of the silica particles... -The presence of hydroxyl groups reduces the surface dissolution of silica particles caused by excessive dissolution of silica particles when the composition is prepared. As a result, the aggregation of silica particles in the aqueous medium (water) is suppressed, the grinding speed is increased when the composition containing silica particles is used for grinding silicon wafers, and the storage stability of the composition is improved.

[0068] The principle of this method (pulse NMR) is based on the fact that solvent molecules in contact with or adsorbed on the particle surface and solvent molecules in the solvent bulk (free solvent molecules that are not in contact with the particle surface) respond differently to changes in the magnetic field.

[0069] If a change in the magnetic field is applied to liquid molecules, energy transfer occurs during the transition from the excited state to the ground state. Typically, liquid molecules (solvent molecules) adsorbed on the particle surface undergo energy transfer via the particle, while liquid molecules (solvent molecules) in the bulk liquid, lacking a transit medium, are less likely to undergo energy transfer. Consequently, the NMR relaxation time of liquid molecules (solvent molecules) adsorbed on the particle surface is shorter than that of molecules in the bulk liquid.

[0070] In addition, the relaxation time measured with silica particle dispersion (e.g., silica particle aqueous dispersion) is the average of two relaxation times, reflecting the liquid volume concentration on the surface of silica particles and the liquid volume concentration in the free state (liquid that is in the bulk liquid but not adsorbed on the particle surface).

[0071] Here, the relaxation time constant R is the reciprocal of the relaxation time T, which is obtained by Rav = (Ps * Rs) + (Pb * Rb).

[0072] Rav is the average relaxation time constant, which is the reciprocal of the relaxation time of the silica particle dispersion (e.g., an aqueous dispersion of silica particles).

[0073] Ps is the volume concentration of the liquid on the particle surface, i.e., the volume concentration of the silica particle dispersion (e.g., silica particle aqueous dispersion).

[0074] Rs is the relaxation time constant of the liquid molecules adsorbed on the particle surface, that is, the reciprocal of the relaxation time of the liquid molecules adsorbed on the particle surface.

[0075] Pb is the volume concentration of the bulk solution, that is, the volume concentration of the blank solution after removing the silica particles from the silica particle dispersion (e.g., a silica particle aqueous dispersion). (In this invention, for example, pure water is used in the case of an aqueous dispersion, and a solvent with a pre-mixed composition ratio of the solvent is used in the case of an organic solvent dispersion or a mixed solvent dispersion of water and organic solvent.)

[0076] Rb is the relaxation time constant of the bulk liquid molecules, which is the reciprocal of the relaxation time of the blank solution (e.g., pure water).

[0077] The pulse NMR values ​​of the silica particle dispersion (e.g., aqueous silica particle dispersion) are calculated as Rsp = (Rav - Rb) / (Rb).

[0078] Rav and Rb are the reciprocals of the relaxation time (transverse relaxation time T2, specifically, the NMR relaxation time after dispersing silica abrasive particles and the NMR relaxation time of a blank solution (e.g., pure water)) measured using a pulsed NMR apparatus (trade name) manufactured by Xigo Nanotools.

[0079] The measurement conditions can be set as follows: magnetic field: 0.3T, measurement frequency: 13MHz, measurement nucleus: 1 H NMR, determination method: CPMG pulse sequence method, sample volume: 0.77 mL, temperature: 30℃.

[0080] Rsp serves as an indicator of the affinity of the particle surface for the solvent. Furthermore, given the same specific surface area of ​​silica particles, a higher Rsp value indicates a higher affinity for the solvent, especially when the solvent is aqueous, indicating higher hydrophilicity.

[0081] <Particle size <Average primary particle size, average secondary particle size>>

[0082] The average primary particle size of colloidal silica dispersion refers to the average primary particle size of silica particles that form the dispersed phase.

[0083] In this invention, unless otherwise specified, the average primary particle size of colloidal silica dispersion (silica particles) refers to the particle size converted from the specific surface area obtained by nitrogen adsorption method (BET method).

[0084] The specific surface area diameter (average particle size D (nm)) obtained by nitrogen adsorption method (BET method) is compared with the specific surface area S (m²) obtained by nitrogen adsorption method. 2 / g) is given by the formula D(nm) = 2720 / S.

[0085] In this invention, the average primary particle size of the silica particles is, for example, 20-100 nm, and may also be, for example, 20-85 nm, 30-70 nm, or 35-60 nm. With an average primary particle size of 20 nm or more, the silica particles come into contact with both the silicon wafer and the polishing pad during silicon wafer polishing, thus increasing the polishing speed. Furthermore, it suppresses the excessive movement distance of the silica particles caused by Brownian motion, thereby reducing the frequency of contact between the silica particles in the polishing composition and improving storage stability. With an average primary particle size of 100 nm or less, it reduces the generation of defects caused by scratches resulting from frictional adhesion of silica particles to the silicon wafer surface during polishing. Additionally, since it prevents silica particles from settling in the polishing composition and adhering to each other at the bottom of the storage container, the storage stability of the polishing composition is improved.

[0086] Furthermore, the average secondary particle size of silica particles in the silica particle dispersion or the grinding composition can be determined by using dynamic light scattering to determine whether the silica particles are in a dispersed state or an aggregated state.

[0087] The average secondary particle size represents the average secondary particle size (dispersed particle diameter). It is generally believed that the average secondary particle size in a completely dispersed state is about 1.2 to 2 times the average primary particle size (the specific surface area diameter obtained by nitrogen adsorption method (BET method) or Sears method, representing the average primary particle size). Moreover, the larger the value of average secondary particle size / average primary particle size, the more concentrated the silica particles in the medium are.

[0088] In this invention, the average secondary particle size of the silica particles, such as colloidal silica dispersions (colloidal silica particles), measured by dynamic light scattering, is, for example, 40-200 nm, or can be set to 40-150 nm, 40-100 nm, or 50-80 nm. By using the average secondary particle size within this range, the aggregation of silica particles in the polishing composition can be suppressed. As a result, while further increasing the polishing speed for polishing silicon wafers, the storage stability of the polishing composition can also be improved. Furthermore, in this invention, the average secondary particle size of the silica particles measured by dynamic light scattering is determined according to ISO 22412:2017 using a Zetasizer Nano (manufactured by Malvern Panalytical). Additionally, the average secondary particle size refers to the Z-average particle size measured by dynamic light scattering.

[0089] <Polyvalent metal impurities>

[0090] Regarding the grinding composition containing an aqueous dispersion of silica particles according to the present invention, the amount of polyvalent metal impurities contained in the grinding composition can be set to 1~100ppm / SiO2, 1~50ppm / SiO2, or 1~40ppm / SiO2.

[0091] Regarding the silica particle dispersion of the present invention, the amount of polyvalent metal impurities contained in the silica particle dispersion can be set to 1~100ppm / SiO2, 1~50ppm / SiO2, or 1~40ppm / SiO2.

[0092] By limiting the amount of polyvalent metal impurities contained in the grinding composition to the range described above, it is possible to suppress changes in the pH value or electrolyte concentration of the grinding composition caused by the leaching of polyvalent metal impurities from the silica particles, or the deterioration of the dispersion stability of silica particles caused by the cationized polyvalent metals in the grinding composition acting as coagulants for silica particles.

[0093] By limiting the amount of polyvalent metal impurities contained in the silica particle dispersion to the specified range, it is possible to suppress changes in the pH value or electrolyte concentration of the silica particle dispersion caused by the dissolution of polyvalent metal impurities from the silica particles, or the deterioration of the dispersion stability of silica particles caused by the cationized polyvalent metals in the silica particle dispersion acting as coagulants for the silica particles.

[0094] Furthermore, by controlling the amount of polyvalent metal impurities contained in the silica particle dispersion to within the aforementioned range, the amount of polyvalent metal impurities in the silica particles can be controlled, resulting in a denser Si-O-Si bond network constituting the silica particle framework and suppressing excessive dissolution of the silica particle surface caused by hydroxyl groups. As a result, while further increasing the polishing speed for silicon wafer polishing, the storage stability of the polishing composition can also be improved.

[0095] Examples of polyvalent metal impurities include iron, aluminum, calcium, magnesium, titanium, zirconium, copper, nickel, chromium, zinc, and lead. Analysis of the amount of polyvalent metal impurities can be performed by pretreating the grinding composition or silica particle dispersion to completely dissolve the silica particles, followed by inductively coupled plasma optical emission spectrometry (ICP-OES), inductively coupled plasma mass spectrometry (ICP-MS), or atomic absorption spectrometry (AA).

[0096] Pretreatment for dissolving silica particles can be performed, for example, by the following steps: For 1 g of silica particles contained in the grinding composition or silica particle dispersion, add 36 mL of 38% hydrofluoric acid aqueous solution, 6 mL of 61% nitric acid, and 0.3 mL of 96% sulfuric acid. Treat the resulting mixed solution at 210°C for 15 minutes using a microwave sample pretreatment device to dissolve the silica particles. Then, recover the decomposed solution. Heat the recovered decomposed solution at 120°C under atmospheric pressure until the solvent evaporates and the solution is dried to obtain a solid. Add 0.3 mL of 61% nitric acid to the obtained solid, and then add pure water so that the total mass of the solid, nitric acid, and pure water is 3 g, to obtain a sample for metal impurity analysis.

[0097] <Silanol group content>

[0098] The silica particles contained in the grinding composition or silica particle dispersion of the present invention may have a specified amount of silanol groups. That is, for silica particle powder obtained by removing the dispersion medium by freeze-drying a colloidal silica dispersion containing the silica particles at room temperature under a pressure of less than 5 Pa, the amount of silanol groups, calculated by the mass reduction when heated from room temperature to 700°C in thermogravimetric analysis and the molecular weight of water molecules using the following formula, may be set to, for example, 0.1~1.5 mmol / g, 0.3~1.5 mmol / g, 0.5~1.5 mmol / g, 0.3~1.4 mmol / g, 0.5~1.4 mmol / g, 0.3~1.3 mmol / g, or 0.3~1.3 mmol / g.

[0099] Silanol group content (mmol / g) = 2 × (M2 - M1) ÷ M H2O ÷ (M0-M1)×1000

[0100] Where M0 represents the mass of silica powder used for the heating weight analysis before heating, M1 represents the mass reduction at the time point of reaching 200℃, and M2 represents the mass reduction at the time point of reaching 700℃. H2O This indicates the molecular weight of a water molecule.

[0101] Furthermore, in order to obtain silica particle powder by freeze-drying, firstly, the silica particle dispersion to be obtained is sequentially contacted with a cation exchange resin, an anion exchange resin, and another cation exchange resin to obtain an ion exchange solution. This ion exchange solution can be frozen at a temperature of -70°C to -80°C, and then freeze-dried at room temperature under a pressure of less than 5 Pa to remove the dispersion medium, thereby obtaining the target silica particle powder.

[0102] Silanol groups exist on the surface of silica particles, and these groups readily adsorb water through hydrogen bonds. Therefore, in order to quantify the amount of silanol groups in silica particles based on the mass reduction caused by heating, it is preferable to heat to approximately 200°C, as described above, to remove the adsorbed water.

[0103] Furthermore, if the amount of silanol groups in the silica particles is greater than the aforementioned amount, for example, 1.5 mmol / g, then when two silica particles come into contact, they are prone to bonding, leading to a deterioration in the stability of the grinding composition or silica particle dispersion. If the amount of silanol groups in the silica particles is less than the aforementioned amount, for example, 0.1 mmol / g, then the surface of the silica particles is not sufficiently solvated in polar solvents, thus failing to maintain dispersibility and agglomerating and precipitating, thereby deteriorating the stability of the grinding composition or silica particle dispersion.

[0104] <density>

[0105] The silica particles contained in the grinding composition or silica particle dispersion of the present invention can have a specified density. That is, the silica particle powder obtained by freeze-drying the colloidal silica dispersion containing the silica particles at room temperature under a pressure of less than 5 Pa to remove the dispersion medium, and the density measured by dry density measurement, can be, for example, set to 2.20~2.35 g / cm³. 3 2.22~2.35g / cm 3 2.25~2.35g / cm 3 2.27~2.35g / cm 3 2.25~2.33g / cm 3 2.25~2.30g / cm 3 Or 2.27~2.30g / cm 3 .

[0106] Furthermore, the step of obtaining silica particle powder by freeze-drying is the same as the step of quantitatively recording the <silanol content>.

[0107] The density of the silica particles contained in the grinding composition or silica particle dispersion is 2.20 g / cm³. 3 Above, or 2.25 g / cm 3 The Si-O-Si bond network constituting the framework of silica particles becomes denser, suppressing the adsorption and detachment of impurities such as metal ions. This prevents deterioration of silica particle dispersibility caused by changes in the pH, electrolyte concentration, or compositional balance of the grinding composition or silica particle dispersion. Furthermore, the density of silica particles contained in the grinding composition or silica particle dispersion is 2.35 g / cm³.3 The following method can suppress the sedimentation of silica particles in the polishing composition or silica particle dispersion, thereby preventing the silica particles from agglomerating together or adhering to the container. As a result, while further increasing the polishing speed when polishing silicon wafers, the storage stability of the polishing composition can also be improved.

[0108] <Ratio of specific surface area based on water vapor adsorption method to that based on nitrogen adsorption method>

[0109] The silica particles contained in the grinding composition or silica particle dispersion of the present invention can have a specified ratio of specific surface area based on water vapor adsorption to specific surface area based on nitrogen adsorption. That is, for silica particle powder obtained by heating and drying a colloidal silica dispersion containing such silica particles under atmospheric conditions to remove the dispersion medium, the specific surface area (Sg) based on water vapor adsorption, obtained by BET analysis of the relationship between water vapor adsorption amount and relative humidity, is... H2O ) relative to the specific surface area (S) based on the nitrogen adsorption method (BET method) described in <Particle Size<Average Primary Particle Size, Average Secondary Particle Size>> N2 The ratio of (S) H2O / S N2 For example, it can be set to 0.10~0.65, 0.15~0.65, 0.20~0.65, 0.10~0.60, 0.10~0.50, 0.10~0.40, 0.20~0.60, 0.25~0.60, 0.25~0.50, or 0.25~0.40. Specific surface area (S) based on water vapor adsorption method. H2O The value can be determined by performing BET analysis on the amount of water vapor adsorbed by silica particles measured using a water vapor adsorption-desorption measuring device and the relative humidity in the range of 0.20 to 0.35 relative humidity.

[0110] Furthermore, in order to obtain silica particle powder by the aforementioned heating and drying, firstly, the silica particle dispersion to be obtained is sequentially contacted with a cation exchange resin, an anion exchange resin, and another cation exchange resin to obtain an ion exchange solution. After removing most of the dispersion medium by heating the ion exchange solution at 140°C for 2 hours, it is then heated at 290°C for 1 hour to completely remove the dispersion medium. Finally, the mixture is pulverized in a mortar for 10 minutes, thereby obtaining the target silica particle powder.

[0111] Similar to the quantification of <silanol group content>, silanol groups exist on the surface of silica particles, and these groups readily adsorb water via hydrogen bonds. Therefore, in order to quantify the specific surface area based on the water vapor adsorption method, it is preferable to remove the adsorbed water by heating at 200°C for 1 hour just before the measurement, as described above.

[0112] Furthermore, if the ratio of the specific surface area based on water vapor adsorption to that based on nitrogen adsorption is greater than the aforementioned, for example, 0.65, then the surface of the silica particles has high hydrophilicity, and the hydroxyl groups (OH groups) in the composition... - Silica particles are largely adsorbed onto the particle surface, and sometimes the silanol groups on the surface of the silica particles crack and dissolve. If the silica particles dissolve, the highly reactive silanol groups inside the silica particles are exposed on the surface, causing the silica particles to aggregate and develop, potentially deteriorating the storage stability of the grinding composition or silica particle dispersion. On the other hand, if the concentration is less than the above, for example, 0.10, the hydrophilicity of the silica particle surface is low, and it is not sufficiently solvated in polar solvents, thus failing to maintain dispersibility, causing aggregation and precipitation, and therefore potentially deteriorating the stability of the grinding composition or silica particle dispersion.

[0113] <Preparation of Silica Particle Dispersion>

[0114] The manufacturing method of the colloidal silica dispersion (silica sol) used in this invention can be roughly divided into: a step of obtaining active silicic acid (I), a step of preparing precursor silica sol (II), a step of further heating the precursor silica sol (III), and a step of concentrating the obtained silica sol (IV).

[0115] [Process (I)]

[0116] The process (I) for obtaining active silicic acid is divided into a process (a1) for obtaining active silicic acid and a process (a2) for purifying it. Of the above processes, process (a1) is necessary, while process (a2) is not necessary but can be performed as needed.

[0117] For example, process (a1) and process (a2) can be implemented as follows.

[0118] Step (a1): An aqueous solution of alkali metal silicate containing metal oxides other than silica at a ratio of 300 to 10,000 ppm relative to silica is diluted with pure water to make the SiO2 component derived from silicate reach a concentration of 1 to 6% by mass. Then, it is contacted with a hydrogen-form strong acid cation exchange resin to obtain an aqueous solution of active silicic acid with a SiO2 concentration of 1 to 6% by mass.

[0119] Step (a2): An acid selected from inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, or phosphoric acid is added to the aqueous solution of active silicic acid obtained in step (a1) to adjust the pH value to 1-2, and the solution is left to stand for at least 12 hours. This dissolves and ionizes metal oxides other than silicon dioxide. The dissolved metal ions are then removed by contacting the solution with a hydrogen-form strongly acidic cation exchange resin, and the anions are removed by contacting the solution with a hydrogen-form strongly basic anion exchange resin, resulting in purified active silicic acid with a SiO2 concentration of 1-6% by mass.

[0120] In step (a1), sodium silicate, which is an inexpensive industrial product, is preferably used as an alkali metal silicate and has a SiO2 / Na2O molar ratio of about 2 to 4. Among the impurities contained in this silicate, the most abundant polyvalent metals are aluminum, iron, calcium, and magnesium.

[0121] To bring the aqueous solution of alkali metal silicate into contact with the hydrogen-form strong acid cation exchange resin, this can be preferentially achieved by passing the aqueous solution of alkali metal silicate through a column packed with the ion exchange resin. The column pass solution is recovered as an aqueous solution of active silicic acid with a SiO2 concentration of 1-6% by mass, preferably 2-6% by mass.

[0122] The amount of hydrogen-form cation exchange resin used can be sufficient to exchange the total amount of alkali metal ions in the aqueous solution of alkali metal silicates with hydrogen ions. Specifically, the exchange capacity of the hydrogen-form cation exchange resin is preferably 1 to 5 times, 1 to 3 times, or 1 to 2 times the total amount of alkali metal ions contained in the aqueous solution of alkali metal silicates, on an equivalent basis. The velocity passing through the column is preferably a space velocity of about 1 to 10 per hour.

[0123] [Process (II)]

[0124] The process of preparing precursor silica sol (II) is, for example, the process of performing the following processes (b) and (c), or the process of preparing commercially available silica sol.

[0125] Step (b): Add an aqueous solution of sodium or potassium hydroxide to the aqueous solution of active silicic acid obtained in step (I) to obtain a stabilized aqueous solution of active silicic acid with a SiO2 concentration of 1 to 6% by mass and a pH of 7 to 10.

[0126] Step (c): The aqueous solution of active silicic acid recovered in step (b) is heated for 0.5 to 30 hours with full stirring, keeping the temperature above 110°C and below 160°C, 110~150°C, 120~150°C, or 130~150°C, to obtain the precursor silica sol.

[0127] Furthermore, the aqueous solution of sodium hydroxide or potassium hydroxide used in step (b) is preferably obtained by dissolving commercially available industrial sodium hydroxide or potassium hydroxide with a purity of 95% by mass or higher in industrial water or ion-exchange water in a concentration preferably 2 to 20% by mass after removing cations.

[0128] In addition, the apparatus used in process (c) can be a conventional apparatus equipped with a stirrer, temperature control device, liquid level sensing device, pressure reducing device, liquid supply device, cooling device, etc., in a container that is resistant to acid, alkali and pressure.

[0129] Furthermore, in process (c), the liquid temperature inside the container is maintained above 110°C and below 160°C.

[0130] [Process (III)]

[0131] The further heating of the precursor silica sol (III) can be listed as steps (d), (e), and (f) below. Of the above steps, step (f) is necessary, while steps (d) and (e) are not necessary but can be performed as needed.

[0132] Either process (d) or process (e) may be performed before process (f). Either process (d) or process (e) may be performed, either process (d) or process (e) may be performed, or neither process may be performed. If both processes are performed, either process (d) or process (e) may be performed first.

[0133] Step (d): Using a known concentration device such as a concentrator equipped with an ultrafiltration membrane or a vacuum concentrator, the precursor silica sol obtained in step (II) or the pH-adjusted precursor silica sol obtained in step (e) below is concentrated to a SiO2 concentration of 10 to 40 by mass.

[0134] Step (e): An alkaline compound is added to the generating solution to adjust the pH value to 7-10. The generating solution is obtained by contacting the precursor silica sol obtained in step (II) or the precursor silica sol with adjusted SiO2 concentration obtained in step (d) with a hydrogen-form strong acid cation exchange resin.

[0135] Step (f): The precursor silica sol obtained in step (II), the precursor silica sol with SiO2 concentration adjusted obtained in step (d), or the precursor silica sol with pH adjusted obtained in step (e) is heated with thorough stirring and kept at a temperature of, for example, above 140°C and below 300°C, 160~280°C, 160~260°C, 160~240°C, 170~240°C, 180~240°C, or 190~240°C for 0.5~30 hours to obtain silica sol.

[0136] Furthermore, in process (f), the liquid temperature inside the container is maintained above 160°C and below 300°C.

[0137] [Process (IV)]

[0138] Step (IV), which further concentrates the obtained silica sol, is a step that concentrates the silica sol obtained in step (III) to 10-50% by mass. This step (IV) is not mandatory but can be performed as needed. Known concentration devices such as concentrators equipped with ultrafiltration membranes or vacuum concentrators can be used for concentration.

[0139] <additive>

[0140] The grinding composition of the present invention, in addition to including silica particles as abrasives and water as an aqueous medium, may further include at least one additive selected from acidic compounds, basic compounds, water-soluble compounds, chelating agents, oxidizing agents and metal corrosion inhibitors.

[0141] The silica particle dispersion of the present invention, in addition to comprising silica particles and water or an organic solvent or a mixture of water and an organic solvent, may further comprise at least one additive selected from the composition of acidic compounds and basic compounds.

[0142] Furthermore, the mass ratio of the solid component remaining after removing water as an aqueous medium from the grinding composition can be, for example, 0.01-40% by mass, 0.01-30% by mass, 0.01-20% by mass, 0.1-40% by mass, 0.1-20% by mass, or 0.1-15% by mass, and the mass ratio of silica particles in this solid component can be 80-100% by mass or 85-99.9% by mass. Additionally, the mass ratio of silica particles in the grinding composition or silica particle dispersion can be 1-40% by mass, 1-30% by mass, 1-20% by mass, or 3-30% by mass.

[0143] By reducing the solid content after removing the aqueous medium from the grinding composition to 0.01% by mass or more, excessive dissolution of the silica particle surface caused by hydroxyl groups can be suppressed. By reducing the solid content after removing the aqueous medium from the grinding composition to 40% by mass or less, the increased frequency of contact between silica particles caused by the increase in the number of silica particles in the grinding composition and the decrease in the amount of solvent can be prevented, thus suppressing agglomeration. In addition, excessive increase in the viscosity of the grinding composition can be suppressed, thus facilitating handling. As a result, the storage stability of the grinding composition is improved, making storage and transportation easier.

[0144] The amount of solid components in the grinding composition or the silica particle dispersion can be determined, for example, by heating the composition in an electric furnace at 1000°C for 1 hour and weighing the remaining portion (residue).

[0145] Examples of acidic compounds include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, or phosphoric acid, and organic acids such as formic acid, oxalic acid, citric acid, acetic acid, lactic acid, malic acid, malonic acid, succinic acid, tartaric acid, butyric acid, fumaric acid, benzoic acid, glycolic acid, propionic acid, or ascorbic acid. An acidic compound may be used alone, or in combination with two or more of these compounds.

[0146] Examples of such basic compounds include alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonates, and nitrogen-containing basic compounds. A basic compound may be used alone, or in combination of two or more of these compounds.

[0147] Among the alkaline compounds, sodium hydroxide or potassium hydroxide is preferably used as an alkali metal hydroxide. Sodium bicarbonate or potassium bicarbonate is preferably used as an alkali metal bicarbonate. Sodium carbonate or potassium carbonate is preferably used as an alkali metal carbonate. Ammonia or quaternary ammonium salt is preferably used as a nitrogen-containing alkaline compound, and quaternary ammonium compounds are more preferred from the viewpoint of achieving high grinding speeds. Tetramethylammonium hydroxide, ethyltrimethylammonium hydroxide, diethyldimethylammonium hydroxide, tetraethylammonium hydroxide, or tetramethylammonium hydroxide or their salts can be used as quaternary ammonium compounds. Among these, tetraethylammonium hydroxide or its salts are preferred, and tetramethylammonium hydroxide or its salts are more preferred.

[0148] The alkaline compound can be incorporated into the grinding composition in proportions relative to the silica particles, such as 0.1-50% by mass, 0.1-30% by mass, 0.1-10% by mass, 1-50% by mass, 1-30% by mass, or 1-10% by mass. By ensuring the amount of the alkaline compound is within the aforementioned range, excessive increase or decrease in the pH value of the grinding composition can be prevented, thereby improving the stability of the grinding composition.

[0149] By adding these acidic or alkaline compounds, the pH value of the polishing composition of the present invention can be adjusted to a range of 1-12, 1-6, 3-6, 7-12, 7-10, 8-11, or 10-12. By setting the pH value of the polishing composition to the range described above, when the polishing composition is used to polish silicon wafers, the Si bonds on the surface of the silicon wafer are broken by the acid or alkali, making the silicon wafer surface easier to polish by silicon dioxide particles, thereby increasing the polishing speed.

[0150] Furthermore, by adding these acidic or basic compounds, the pH value of the silica particle dispersion of the present invention can be adjusted to a range of 8-11, 8-10, or 9-10. By setting it to such a range, the dispersibility of silica particles is improved, and the aggregation of silica particles in the solvent can be suppressed.

[0151] As the water-soluble compound, any water-soluble compound can be used. Examples include monomers having carboxylic acid groups such as acrylic acid, methacrylic acid, and maleic acid, as polymers thereof such as polyacrylic acid and polymethacrylic acid, and as salts thereof such as ammonium polyacrylate, potassium polyacrylate, ammonium polymethacrylate, and potassium polymethacrylate. Additionally, alginic acid, pectic acid, carboxymethyl cellulose, polyaspartic acid, polyglutamic acid, polyamic acid, ammonium polyamate, polyvinylpyrrolidone, hydroxyethyl cellulose, hydroxypropyl cellulose, glycerol, polyglycerol, polyvinyl alcohol, polyacrylamide and its derivatives, polymethacrylamide and its derivatives, or carboxyl or sulfonic acid modified polyvinyl alcohol, etc., can also be used.

[0152] The water-soluble compound can be incorporated into the polishing composition in proportions relative to the silica particles, such as 0.01-10% by mass, 0.01-5% by mass, 0.01-3% by mass, 0.05-10% by mass, 0.1-10% by mass, or 0.05-5% by mass. By incorporating the water-soluble compound within the aforementioned range, the dispersion stability of the silica particles contained in the polishing composition can be improved, and during the polishing of the silicon wafer, the compound adheres to the silicon wafer, protecting the portion of the silicon wafer surface where the load is concentrated, excluding the protrusions, thereby improving the flatness of the silicon wafer.

[0153] As the chelating agent, an aminocarboxylic acid chelating agent or a phosphonic acid chelating agent can be used.

[0154] Examples of aminocarboxylic acid chelating agents include ethylenediaminetetraacetic acid, hypozinotriacetic acid, diethylenetriaminepentaacetic acid, hydroxyethylethylenediaminetriacetic acid, triethylenetetraaminehexaacetic acid, 1,3-propanediaminetetraacetic acid, 1,3-diamine-2-hydroxypropanetetraacetic acid, hydroxyethyliminodiacetic acid, dihydroxyethylglycine, ethylene glycol ether diaminetetraacetic acid, dicarboxymethylglutamic acid, and ethylenediamine-N,N'-disuccinic acid.

[0155] In addition, examples of phosphonic acid chelating agents include hydroxyethylidene diphosphonic acid, nitrotris(methylenephosphonic acid), phosphonobutanetricarboxylic acid, and ethylenediaminetetra(methylenephosphonic acid).

[0156] The chelating agent can be incorporated into the polishing composition in proportions relative to the silica particles, such as 0.01-10% by mass, 0.01-5% by mass, 0.01-3% by mass, 0.05-10% by mass, 0.1-10% by mass, or 0.05-5% by mass. By incorporating the chelating agent within the aforementioned range, contamination of the silicon wafer caused by metallic impurities can be reduced, and the dispersion stability of the silica particles contained in the polishing composition can be improved.

[0157] Examples of oxidizing agents include hydrogen peroxide, potassium permanganate, potassium periodate, hypochlorous acid, and ozone water.

[0158] The oxidant can be incorporated into the polishing composition in proportions relative to the silicon dioxide particles, such as 0.01-10% by mass, 0.01-5% by mass, 0.01-3% by mass, 0.05-10% by mass, 0.1-10% by mass, or 0.05-5% by mass. By incorporating the oxidant within the aforementioned range, when the polishing composition is used for polishing silicon wafers, the surface of the silicon wafer is oxidized, making it easier for the silicon dioxide particles to remove, thereby increasing the polishing speed.

[0159] Examples of metal corrosion inhibitors include triazole compounds, pyridine compounds, pyrazole compounds, pyrimidine compounds, imidazole compounds, guanidine compounds, thiazole compounds, tetraazole compounds, triazine compounds, and hexamethylenetetramine, etc.

[0160] Examples of triazole compounds include 1,2,3-triazole, 1,2,4-triazole, 3-amino-1H-1,2,4-triazole, benzotriazole (BTA), 1-hydroxybenzotriazole, 1-hydroxypropylbenzotriazole, 2,3-dicarboxypropylbenzotriazole, 4-hydroxybenzotriazole, 4-carboxy-1H-benzotriazole, 4-carboxy-1H-benzotriazole methyl ester (1H-benzotriazole-4-carboxylate methyl ester), 4-carboxy-1H-benzotriazole butyl ester (1H-benzotriazole-4-carboxylate butyl ester), 4-carboxy-1H-benzotriazole octyl ester (1H-benzotriazole-4-carboxylate octyl ester), 5-hexylbenzotriazole, (1,2,3-benzotriazolyl-1-methyl)(1,2,4-triazolyl-1-methyl)(2-ethylhexyl)amine, and toluenetriazole. Naphthotriazole, bis[(1-benzotriazolyl)methyl]phosphonic acid, 3H-1,2,3-triazol[4,5-b]pyridine-3-ol, 1H-1,2,3-triazol[4,5-b]pyridine, 1-acetyl-1H-1,2,3-triazol[4,5-b]pyridine, 3-hydroxypyridine, 1,2,4-triazol[1,5-a]pyrimidine, 1,3,4,6,7, 8-Hexahydro-2H-pyrimidino[1,2-a]pyrimidine, 2-methyl-5,7-diphenyl-[1,2,4]triazolo[1,5-a]pyrimidine, 2-methylthioalkyl-5,7-diphenyl-[1,2,4]triazolo[1,5-a]pyrimidine, 2-methylthioalkyl-5,7-diphenyl-4,7-dihydro-[1,2,4]triazolo[1,5-a]pyrimidine, etc.

[0161] Examples of pyridine compounds include pyridine, 8-hydroxyquinoline, propionylisocyanate, 2-nitropyridine-3-ol, pyridoxine, nicotinamide, isonicoylisopropylhydrazine, isonicoic acid, benzo[f]quinoline, 2,5-pyridinedicarboxylic acid, 4-styrylpyridine, neonicotinoid, 4-nitropyridine-1-oxide, acetic acid-3-ethyl pyridine, quinoline, 2-ethylpyridine, quinoline acid, arecoline, citric acid, pyridine-3-methanol, 2-methyl-5-ethylpyridine, 2-fluoropyridine, pentafluoropyridine, 6-methylpyridine-3-ol, acetic acid-2-ethyl pyridine, etc.

[0162] Examples of pyrazole compounds include pyrazole, 1-allyl-3,5-dimethylpyrazole, 3,5-bis(2-pyridyl)pyrazole, 3,5-diisopropylpyrazole, 3,5-dimethyl-1-hydroxymethylpyrazole, 3,5-dimethyl-1-phenylpyrazole, 3,5-dimethylpyrazole, 3-amino-5-hydroxypyrazole, 4-methylpyrazole, N-methylpyrazole, and 3-aminopyrazole.

[0163] Examples of pyrimidine compounds include pyrimidines, 1,3-diphenyl-pyrimidine-2,4,6-trione, 1,4,5,6-tetrahydropyrimidine, 2,4,5,6-tetraaminopyrimidine sulfate, 2,4,5-trihydroxypyrimidine, 2,4,6-triaminopyrimidine, 2,4,6-trichloropyrimidine, 2,4,6-trimethoxypyrimidine, 2,4,6-triphenylpyrimidine, 2,4-diamino-6-hydroxypyrimidine, 2,4-diaminopyrimidine, 2-acetamide pyrimidine, 2-aminopyrimidine, and 4-aminopyrazolo[3,4-d]pyrimidine.

[0164] Examples of imidazole compounds include imidazole, 1,1'-carbonylbis-1H-imidazole, 1,1'-oxalyldiimidazole, 1,2,4,5-tetramethylimidazole, 1,2-dimethyl-5-nitroimidazole, 1,2-dimethylimidazole, 1-(3-aminopropyl)imidazole, 1-butylimidazole, 1-ethylimidazole, 1-methylimidazole, benzimidazole, etc.

[0165] Examples of guanidine compounds include guanidine, 1,1,3,3-tetramethylguanidine, 1,2,3-triphenylguanidine, 1,3-di-o-tolylguanidine, and 1,3-diphenylguanidine.

[0166] Examples of thiazole compounds include thiazole, 2-mercaptobenzothiazole, and 2,4-dimethylthiazole.

[0167] Examples of the tetrazolium compounds include tetrazolium, 5-methyltetrazole, 5-amino-1H-tetrazole, and 1-(2-dimethylaminoethyl)-5-mercaptotetrazole.

[0168] Examples of triazine compounds include triazine, 3,4-dihydro-3-hydroxy-4-oxo-1,2,4-triazine, etc.

[0169] The metal corrosion inhibitor can be incorporated into the polishing composition at a ratio of, for example, 0.0001 to 10% by mass relative to the silica particles. By ensuring that the amount of metal corrosion inhibitor is within this range, the corrosion protection effect can be maintained and the stability of the polishing composition can be improved.

[0170] <Stability of Grinding Compositions: Heating and Storage Test>

[0171] In a test where the grinding composition of the present invention is heated and stored at 50°C for 28 days, it is preferable that the increase rate of the average secondary particle size of the grinding composition after heating and storing at 50°C for 28 days is low (no change in particle size) compared to the average secondary particle size of the grinding composition before heating and storage. For example, it can be set to less than 5%, or an increase rate of 4% or less, 0% or more and less than 5%, 0 to 4%, or 0 to 3%.

[0172] The grinding composition that meets the aforementioned increase rate has almost no change in the particle size and shape of the silica particles contained in it, even after transportation or storage. Therefore, it does not produce coarse particles due to the aggregation of silica particles or reduce the amount of effective ingredients due to the sedimentation of silica particles, and can achieve the desired grinding performance.

[0173] The grinding composition of the present invention can be manufactured, stored, and transported in the form of a concentrated solution. The silica concentration in the concentrated solution is not particularly limited, as long as it meets the increase rate of the average secondary particle size during a test of heating and storing at the stated 50°C for 28 days. For example, it can be set to 1-30% by mass, 5-30% by mass, 5-25% by mass, or 10-25% by mass. By manufacturing, storing, and transporting it in the form of a concentrated solution, transportation costs can be reduced, and space can be saved during storage. The concentrated solution can be diluted with any solvent such as pure water before use to adjust to a specified SiO2 concentration, for example, 0.1-10% by mass, before being used for grinding. Furthermore, by setting the SiO2 concentration of the concentrated solution within the range that meets the stated increase rate, the reduction in grinding performance caused by the agglomeration of silica particles contained in the concentrated solution can be suppressed.

[0174] The pH value of the concentrate can be adjusted to a range of 1~12, 1~6, 3~6, ​​7~12, 7~10, 8~12, 9~12, 10~12, or 11~12.

[0175] The polishing composition of the present invention can be used for polishing silicon wafers or device wafers. Polishing apparatuses include single-sided polishing and double-sided polishing methods, and the polishing composition of the present invention can be used to polish silicon wafers in either type of apparatus. The polishing process of silicon wafers is typically structured as a multi-stage polishing process, including primary polishing performed at the beginning of the polishing process and fine polishing performed after the primary polishing process. Furthermore, primary polishing and fine polishing may each be performed in two stages. The polishing composition of the present invention can be used in both primary polishing and fine polishing, or it can be used only in either primary polishing or fine polishing. The polishing composition of the present invention can be circulated within the polishing apparatus during each polishing process, or it can be used in a non-circulating flow method for single-use. Furthermore, the polishing composition of the present invention can also be used for CMP polishing of device wafers.

[0176] The silica particle dispersion of the present invention is well suited for use in grinding compositions.

[0177] [Example]

[0178] The present invention will now be described in more detail through examples. However, the present invention is not limited thereto.

[0179] 1) Synthesis of colloidal silica dispersion

[0180] (Synthesis Example 1) Synthesis of Colloidal Silica Dispersion A

[0181] A water-soluble alkali metal silicate, JIS 3 standard sodium silicate aqueous solution, was prepared as the raw material. In this sodium silicate aqueous solution, the main components other than water were SiO2 (28.8% by mass) and Na2O (9.47% by mass).

[0182] The sodium silicate aqueous solution was diluted with pure water to prepare a sodium silicate aqueous solution with a SiO2 concentration of 4% by mass (a).

[0183] Next, the sodium silicate aqueous solution (a) was passed through a column filled with hydrogen-form strong acid cation exchange resin (trade name) Amberlite IR-120B at a space velocity of 4.5 per hour to remove cations, thereby producing an active silica aqueous solution.

[0184] A 10% (w / w) sodium hydroxide aqueous solution was added to the obtained active silicic acid aqueous solution to adjust the pH to 8.5-9.5, thereby obtaining a stabilized active silicic acid aqueous solution. The SiO2 concentration of the obtained stabilized active silicic acid aqueous solution was 3.2% (w / w).

[0185] 2400 g of the stabilized aqueous solution of active silica obtained above was added to a reaction apparatus equipped with a stirrer and heating device in a 3 L SUS (stainless steel) pressure-resistant container. The liquid temperature inside the container was adjusted to 130-150 °C by heating. After the temperature inside the container reached 130-150 °C, the container was heated for 2 hours and 30 minutes while maintaining the temperature at 130-150 °C, thereby obtaining a colloidal silica dispersion (precursor silica sol) with an average primary particle size of 10-15 nm.

[0186] Using a commercially available ultrafiltration apparatus equipped with an ultrafiltration membrane made of polysulfone with a molecular weight cutoff of 200,000 (Advantech Co., Ltd. (trade name) Q2000 150E), the obtained colloidal silica dispersion was concentrated at room temperature to a SiO2 concentration of 33% by mass, thereby obtaining a precursor silica sol with adjusted SiO2 concentration.

[0187] The precursor silica sol with adjusted SiO2 concentration was passed through a column filled with hydrogen-form strong acid cation exchange resin (trade name) Amberlite IR-120B at a space velocity of 10 per hour to remove cations. 10% by mass of sodium hydroxide aqueous solution was added to the resulting dispersion to adjust the pH to 7-8, thus obtaining a precursor silica sol with adjusted pH.

[0188] The precursor silica sol, with its SiO2 concentration and pH adjusted as described above, was added to a reaction apparatus equipped with a stirrer and heating device in a 3L SUS pressure vessel. The liquid temperature inside the vessel was adjusted to 220-240°C by heating. After the temperature inside the vessel reached 220-240°C, the vessel was heated for 2 hours and 20 minutes while maintaining the temperature at 220-240°C, thereby obtaining colloidal silica dispersion A.

[0189] (Synthesis Example 2) Synthesis of Colloidal Silica Dispersion B

[0190] Except for heating the precursor silica sol, whose SiO2 concentration and pH value were adjusted, in a pressure vessel made of SUS at a temperature of 210~230°C, the colloidal silica dispersion B was obtained by the same operation as in Synthesis Example 1.

[0191] (Synthesis Example 3) Synthesis of Colloidal Silica Dispersion C

[0192] The colloidal silica dispersion B obtained in Synthesis Example 2 was passed through a column filled with hydrogen-form strong acid cation exchange resin (trade name) Amberlite IR-120B at a space velocity of 10 per hour to remove cations. A 10% by mass aqueous solution of sodium hydroxide was added to the resulting dispersion to adjust the pH to 9-10.

[0193] 2400g of the colloidal silica dispersion B, adjusted to a pH of 9-10, was placed into a reaction apparatus equipped with a stirrer and heating device in a 3L SUS pressure-resistant container. The liquid temperature inside the container was adjusted to 190-210°C by heating. After the temperature inside the container reached 190-210°C, it was heated for 12 hours while maintaining the temperature at 190-210°C, thereby obtaining colloidal silica dispersion C.

[0194] (Synthesis Example 4) Synthesis of Colloidal Silica Dispersion D

[0195] Except for heating the colloidal silica dispersion B, which was adjusted to a pH of 9-10, at a temperature of 170-190°C for 72 hours using a SUS pressure vessel, the same procedure as in Synthesis Example 3 was used to obtain the colloidal silica dispersion D.

[0196] (Synthetic Example 5) Synthesis of Colloidal Silica Dispersion E

[0197] Except for heating the precursor silica sol with adjusted SiO2 concentration and pH value in a SUS pressure vessel at 230~250°C for 6 hours, the colloidal silica dispersion E was obtained by the same procedure as in Synthesis Example 1.

[0198] (Synthetic Example 6) Synthesis of Colloidal Silica Dispersion F

[0199] Except for heating the precursor silica sol with adjusted SiO2 concentration and pH value in a SUS pressure vessel at 240~260°C for 9 hours, the colloidal silica dispersion F was obtained by the same procedure as in Synthesis Example 1.

[0200] (Synthesis Example 7) Synthesis of Colloidal Silica Dispersion G

[0201] Colloidal silica dispersion G was synthesized by proceeding in the same manner as in Synthesis Example 4 of International Publication No. 2020 / 091000.

[0202] Specifically, 8% by mass of sulfuric acid was added to the aqueous solution of active silicic acid obtained using the same procedure as in Synthesis Example 1, and the pH was adjusted to 2-3, thereby obtaining an aqueous solution of active silicic acid stabilized with sulfuric acid. While stirring, pure water was added to the aqueous solution of active silicic acid stabilized with sulfuric acid obtained above, followed by the addition of 10% by mass of potassium hydroxide aqueous solution, thereby adjusting the SiO2 concentration to 3.2% by mass and the pH to 12.0. The liquid temperature inside the container was then adjusted to 110-130°C using a reaction apparatus equipped with a stirrer, heating device, etc., in a 3L SUS pressure-resistant container. Once the temperature inside the container reached 110-130°C, while maintaining the temperature at 110-130°C, the aqueous solution of active silicic acid stabilized with sulfuric acid obtained above was continuously supplied as the feed solution until the pH of the reaction solution reached 11.4. After supplying an aqueous solution of active silicic acid stabilized with sulfuric acid, the temperature inside the container is maintained at 110°C, and the reaction is carried out for 1 hour. Then, the aqueous solution of active silicic acid stabilized with sulfuric acid is continuously supplied until the pH of the reaction solution reaches 11.1. After supplying the aqueous solution of active silicic acid stabilized with sulfuric acid, the temperature inside the container is maintained at 110~130°C while heating for another 2 hours, thereby obtaining the reaction solution.

[0203] The obtained reaction solution was concentrated at room temperature to a SiO2 concentration of 40% by mass using a commercially available ultrafiltration device equipped with a polysulfone ultrafiltration membrane (Advantech Co., Ltd. (trade name) Q2000 150E) with a molecular weight cutoff of 200,000, thereby obtaining a colloidal silica dispersion G.

[0204] (Synthetic Example 8) Synthesis of Colloidal Silica Dispersion H

[0205] 2400g of colloidal silica dispersion (trade name PL-3) manufactured by Fuso Chemical Industry Co., Ltd. was placed into a reaction apparatus equipped with a stirrer, heating device, etc., in a 3L SUS pressure-resistant container, and the temperature was adjusted to 190~210°C. After the temperature inside the container reached 190~210°C, it was heated for 1 hour while maintaining the temperature inside the container at 190~210°C, thereby obtaining colloidal silica dispersion H.

[0206] (Synthesis Example 9) Synthesis of Colloidal Silica Dispersion I

[0207] Except for maintaining the temperature inside the container at 190~210°C for 5 hours, colloidal silica dispersion I was obtained by the same procedure as in synthesis example 6.

[0208] 2) Analysis of colloidal silica dispersion and silica particles

[0209] The prepared colloidal silica dispersions A to I, and the colloidal silica dispersions manufactured by Nissan Chemical Co., Ltd. (trade name) The following analysis was performed on a colloidal silica dispersion (trade name PL-3) manufactured by Fuso Chemical Industry Co., Ltd.

[0210] 2-1) Methods for determining particle size

[0211] The average primary particle size of silica particles was determined by nitrogen adsorption.

[0212] Pure water was added to each colloidal silica dispersion to prepare samples with SiO2 concentration adjusted to 10% by mass. Then, 5g of the obtained sample was added to 10mL of hydrogen-form strong acid cation exchange resin Amberlite (trade name) IR-120B and stirred for 30 minutes to obtain a sample with cations removed.

[0213] After removing the cation exchange resin by filtering the obtained sample through a nylon mesh, the solvent was removed by heating it at 290°C for 1 hour in an atmospheric atmosphere using an electric furnace (trade name DX302, manufactured by Yamato Science Co., Ltd.) to obtain a dried product. The dried product was then ground in an agate mortar for 10 minutes to obtain a heat-dried powder.

[0214] The heated and dried powder was used as the test sample, and the nitrogen-based specific surface area S of the test sample was determined using a Monosorb (trade name) instrument (manufactured by Konta Instruments Japan Contract Co., Ltd.) and the nitrogen adsorption method (BET method). N2 The average primary particle size is then calculated from the obtained specific surface area value.

[0215] In addition, the average secondary particle size of silica particles was determined using dynamic light scattering (DLS) with Zetasizer Nano (manufactured by Malvern Panalytical) as follows: 0.1 g of colloidal silica dispersion was taken into a polystyrene cell with a light path length of 10 mm, and then 0.15% by mass of sodium chloride aqueous solution was added to obtain a colloidal silica dispersion with the silica concentration adjusted to a count rate of 200-400 kcps at an attenuator of 7. The amount of this adjusted colloidal silica dispersion added to the cell was adjusted so that the height of the liquid surface from the bottom of the cell was about 1 cm, and the average secondary particle size of silica was measured under the conditions of attenuator 7 and temperature of 22.0 °C.

[0216] 2-2) Analysis methods of pulsed NMR

[0217] Pure water was added to each colloidal silica dispersion to prepare samples with a SiO2 concentration adjusted to 5% by mass. 0.77 mL of this sample was loaded into a glass NMR tube, and the relaxation time of the sample was determined using a pulsed NMR apparatus (trade name) Acorn area manufactured by Xigo Nanotools under the following conditions.

[0218] Magnetic field: 0.3T

[0219] Measurement frequency: 13MHz

[0220] Measurement nucleus: 1 H NMR

[0221] Measurement method: CPMG pulse sequence method

[0222] Temperature: 30℃

[0223] The reciprocal of the relaxation time of the colloidal silica dispersion obtained under the conditions is denoted as Rav, and the reciprocal of the relaxation time of pure water obtained under the same conditions is denoted as Rb. The Rsp value of each colloidal silica dispersion is calculated using the following formula.

[0224] Rsp = (Rav - Rb) / (Rb)

[0225] 2-3) Quantitative methods for the amount of silanol groups

[0226] Pure water was added to each colloidal silica dispersion to prepare samples with a SiO2 concentration adjusted to 10% by mass. Next, 100g of the obtained sample was added to 20mL of Amberlite (trade name) IR-120B hydrogen-form strong acid cation exchange resin, and stirred for 30 minutes to remove cations. After removing the cation exchange resin by filtering the obtained sample through a nylon mesh, 20mL of Amberlite (trade name) IRA-410 hydroxyl-form strong basic anion exchange resin was added, and stirred for 30 minutes to remove anions. After removing the anion exchange resin by filtering the obtained sample through a nylon mesh, 20mL of Amberlite (trade name) IR-120B hydrogen-form strong acid cation exchange resin was added again, and stirred for 30 minutes to remove cations. Finally, the obtained sample was filtered through a nylon mesh to remove the cation exchange resin, resulting in a dispersion free of cations and anions.

[0227] The deionized dispersion was placed into a 300 mL flask. The flask containing the dispersion was then immersed in ethanol cooled to -70°C to -80°C with dry ice for 10 minutes to obtain a frozen dispersion. The frozen dispersion was then subjected to a freeze-drying apparatus (trade name FDU-2100, manufactured by Tokyo Rikagi K.K. Co., Ltd.) under a vacuum of less than 5 Pa at room temperature, causing the frozen water to sublimate and yield a freeze-dried sample. The freeze-dried sample was then ground in an agate mortar for 10 minutes to obtain a freeze-dried powder.

[0228] The freeze-dried powder was heated using a thermogravimetric differential thermal analysis device (trade name TG-DTA2000SA, manufactured by Bruker) to determine the mass loss when the temperature was increased from room temperature to 700°C.

[0229] Specifically, 5-10 mg of the freeze-dried powder is placed in a platinum container as the initial sample mass M0. The platinum container containing the freeze-dried powder is placed in a thermogravimetric differential calorimeter and heated from room temperature to 700°C at a rate of 10°C / min under a nitrogen atmosphere. Furthermore, the nitrogen flow rate is set to 100 cc / min. The mass reduction M1 at the time point when the temperature inside the apparatus reaches 200°C is considered as the mass reduction caused by the removal of water adsorbed on the surface of the silica particles contained in the freeze-dried powder. The mass reduction M2 at the time point when the temperature inside the apparatus reaches 700°C is considered as the mass reduction caused by the removal of water generated through the dehydration condensation of silanol groups. The amount of silanol groups in the silica particles is calculated using the following formula.

[0230] Silanol content (mmol / g) = 2 × (M2 - M1) ÷ 18 ÷ (M0 - M1) × 1000

[0231] 2-4) Method for determining dry density

[0232] The freeze-dried powder of the colloidal silica dispersion prepared in the same manner as in 2-3) was used as the sample for determining the dry density.

[0233] Using a dry automated density measuring device (trade name AccuPyc II TEC, manufactured by Micromeritics), the test sample was filled to a depth of 1 cm. 3 The dry density of silica particles was determined by gas displacement method at 25°C using an aluminum cell filled to 80% capacity and He gas was used.

[0234] 2-5) Method for determining the ratio of specific surface area based on water vapor adsorption to that based on nitrogen adsorption.

[0235] Pure water was added to each colloidal silica dispersion to prepare samples with a SiO2 concentration adjusted to 10% by mass. Next, 100g of the obtained sample was added to 20mL of Amberlite (trade name) IR-120B hydrogen-form strong acid cation exchange resin, and stirred for 30 minutes to remove cations. After removing the cation exchange resin by filtering the obtained sample through a nylon mesh, 20mL of Amberlite (trade name) IRA-410 hydroxyl-form strong basic anion exchange resin was added, and stirred for 30 minutes to remove anions. After removing the anion exchange resin by filtering the obtained sample through a nylon mesh, 20mL of Amberlite (trade name) IR-120B hydrogen-form strong acid cation exchange resin was added again, and stirred for 30 minutes to remove cations. Finally, the obtained sample was filtered through a nylon mesh to remove the cation exchange resin, resulting in a dispersion free of cations and anions.

[0236] 20 g of the dispersion was weighed into an alumina petri dish and heated at 140°C for 2 hours using a heating plate to remove moisture. The resulting silica powder was then heated in an electric furnace at 290°C for 1 hour to completely dry it. The resulting silica powder was then ground in an agate mortar for 10 minutes to obtain a heat-dried powder.

[0237] The amount of water vapor adsorbed by the heated and dried powder was determined using a water vapor adsorption-desorption apparatus (TA Instruments Japan, trade name Q5000 SA) under the following conditions: nitrogen flow rate was set to 200 mL / min, and the measurement temperature was set to 25°C. Furthermore, just before the measurement, the heated and dried powder was dried in an electric furnace at 200°C for 1 hour to remove adsorbed water, and then 10 mg of sample powder was weighed into a platinum container within 5 minutes for measurement.

[0238] A BET plot was constructed based on the relationship between water vapor adsorption and relative humidity, and an approximate straight line was obtained within the relative humidity range of 0.20–0.35. The slope W of this straight line was then determined. M The specific surface area S of the test sample based on the water vapor adsorption method is calculated using the following formula as the amount of water vapor adsorbed per 1g of the test sample. H2O .

[0239] S H2O =W M ×N A ×A M ÷M H2O

[0240] =W M ×6.02×10 23 ×10.8×10 -20 ÷18

[0241] =W M ×3612

[0242] Here, N A Denotes Avogadro's number, A M M represents the cross-sectional area occupied by each water molecule. H2O This indicates the molecular weight of water.

[0243] Based on the specific surface area S determined above using the water vapor adsorption method H2O And the specific surface area S obtained in 2-1) based on nitrogen adsorption method N2 Calculate their ratio S H2O / S N2 .

[0244] 3) Preparation of grinding composition

[0245] (Example 1)

[0246] Using the colloidal silica dispersion A obtained in Synthesis Example 1, and adding the reagents and pure water, the silica particles derived from the colloidal silica dispersion A were 20.5% by mass, ethylenediaminetetraacetic acid tetrasodium salt was 0.65% by mass, tetramethylammonium hydroxide (TMAH) was 1.0% by mass, and potassium carbonate was 1.5% by mass. The mixture was stirred for 30 minutes to obtain the grinding composition of Example 1.

[0247] (Example 2)

[0248] Except for using the colloidal silica dispersion B obtained in Synthesis Example 2, the grinding composition of Example 2 was prepared in the same manner as in Example 1.

[0249] (Example 3)

[0250] The grinding composition of Example 3 was prepared in the same manner as in Example 1, except that the colloidal silica dispersion C obtained in Synthesis Example 3 was used.

[0251] (Example 4)

[0252] The grinding composition of Example 4 was prepared in the same manner as in Example 1, except that the colloidal silica dispersion D obtained in Synthesis Example 4 was used.

[0253] (Example 5)

[0254] The grinding composition of Example 5 was prepared in the same manner as in Example 1, except that the colloidal silica dispersion E obtained in Synthesis Example 5 was used.

[0255] (Example 6)

[0256] The grinding composition of Example 6 was prepared in the same manner as in Example 1, except that the colloidal silica dispersion F obtained in Synthesis Example 6 was used.

[0257] (Comparative Example 1)

[0258] In addition to using colloidal silica dispersions manufactured by Nissan Chemical Co., Ltd. (trade name: Colloidal silica dispersion) as a colloidal silica dispersion. Except for Example 1, the grinding composition of Comparative Example 1 was prepared in the same manner as in Example 1.

[0259] (Comparative Example 2)

[0260] Except for using the colloidal silica dispersion G obtained in Synthesis Example 7, the same procedure as in Example 1 was followed to prepare the grinding composition of Comparative Example 2.

[0261] (Comparative Example 3)

[0262] Except that a colloidal silica dispersion (trade name PL-3) manufactured by Fuso Chemical Industry Co., Ltd. was used as the colloidal silica dispersion, the same procedure as in Example 1 was followed to prepare the grinding composition of Comparative Example 3.

[0263] (Comparative Example 4)

[0264] Except for using the colloidal silica dispersion H obtained in Synthesis Example 8, the same procedure as in Example 1 was followed to prepare the grinding composition of Comparative Example 4.

[0265] (Comparative Example 5)

[0266] Except for using the colloidal silica dispersion I obtained in Synthesis Example 9, the same procedure as in Example 1 was followed to prepare the grinding composition of Comparative Example 5.

[0267] <Evaluation>

[0268] (Storage stability test)

[0269] Immediately after the preparation of the grinding compositions of Examples 1-6 and Comparative Examples 1-5, the average secondary particle size of the silica particles was measured. Each grinding composition was stored in a commercially available thermostatic bath set to 50°C, and the average secondary particle size was measured after 28 days. Furthermore, the average secondary particle size was determined using the steps described in "2-1) Particle Size Measurement Method" of "2) Analysis of Colloidal Silica Dispersion and Silica Particles" above.

[0270] If the rate of change (increase) of the average secondary particle size after storage at 50°C is less than 5% compared to the average secondary particle size immediately after the grinding composition was prepared (before storage at 50°C), it is judged to have good storage stability.

[0271] (Grinding test)

[0272] The grinding compositions of Examples 1-6 and Comparative Examples 1-5 were diluted 20 times with pure water on a mass basis to obtain grinding test compositions.

[0273] Polishing tests were conducted using the aforementioned polishing test composition under the polishing conditions described below. The wafer being polished was a single-crystal silicon wafer with a diameter of 200 mm, a P-type conductivity, and a Miller index crystal orientation. <100> The resistivity is below 100 Ω·cm. The grinding test composition was supplied in a circulating manner, with a liquid temperature of 23~25℃. The grinding time was 60 minutes per batch, and three batches were ground using the same grinding pad. The grinding solution volume was 25 kg, and no replenishment of new grinding solution or pH adjustment was performed between batches.

[0274] (Grinding conditions)

[0275] Grinding machine: Hamai Sangyo Co., Ltd., product name: Double-sided grinding machine 13BF

[0276] Grinding pad: JH-RHODES Co., Ltd., trade name LP-57, groove width 2mm, groove spacing 20mm

[0277] Grinding load: 150g / cm 2

[0278] Lower platform speed: 6.6 rpm

[0279] Platform speed: 20 rpm

[0280] Rotation ratio: 3.3

[0281] Number of wafers to be ground: Prepare 3 sets of 1 wafer / carrier, and grind a total of 3 wafers simultaneously.

[0282] Feed rate of the composition for the grinding test: 6.4 L / min

[0283] Grinding time: 60 minutes

[0284] Carrier: Epoxy glass carrier (0.70mm thick)

[0285] (Evaluation criteria for polished wafers)

[0286] The grinding rate is calculated by measuring the thickness of the wafer before and after grinding using a laser displacement meter (Keyence Co., Ltd., trade name SI-F1000), subtracting the thickness of the wafer after grinding from the thickness of the wafer before grinding, and then dividing by the grinding time of 60 minutes.

[0287] Surface roughness was measured using a Nikon Solutions BW-M7000 optical interference microscope system (trade name) with a 100x objective lens, measuring the root-mean-square height of a 111μm square region in the center of the wafer.

[0288] (result)

[0289] The physical properties of the colloidal silica dispersions used in Examples 1-6 and Comparative Examples 1-5 are shown in Table 1, and the results of the grinding test and the storage stability test of each grinding composition are shown in Table 2.

[0290]

[0291]

[0292] As shown in Table 2, the grinding speed was 0.32~0.34 μm / min in Examples 1~6 and 0.32~0.33 μm / min in Comparative Examples 1~5, which represents equivalent performance. The surface roughness was 1.09~1.16 nm in Examples 1~6 and 1.13~1.17 nm in Comparative Examples 1~5, which also represents equivalent performance.

[0293] This is believed to be because the silica particles in colloidal silica dispersions A to F with Rsp values ​​of 0.07 to 0.14 have sufficient hydrophilicity to maintain the dispersion of silica particles in the grinding composition. Therefore, in the grinding test, a grinding speed and surface roughness that can uniformly and efficiently remove the silicon wafer surface that has been deteriorated by alkaline components such as TMAH and potassium carbonate were achieved.

[0294] On the other hand, in the storage stability test, in Examples 1-6, where the Rsp value of the colloidal silica dispersion used to prepare the grinding composition was within a specific range, the average secondary particle size change rate was 0-2%, which is considered a good result. This is believed to be because, in the silica particles of the colloidal silica dispersion with an Rsp value of 0.07-0.14, hydroxyl groups (OH groups) confined near the particle surface are... - The low concentration of hydroxyl groups inhibits excessive dissolution of silica particles on their surface, thus suppressing the aggregation of silica particles and resulting in excellent storage stability.

[0295] On the other hand, it is believed that in the grinding compositions of Comparative Examples 1 to 5, which used silica particles with colloidal silica dispersions whose Rsp values ​​were not within a specific range, a large number of hydroxyl groups were present near the surface of the silica particles. It is believed that this easily leads to the dissolution of silica particles, the breaking of Si-O-Si bonds on the surface of silica particles, thus making them active, and the aggregation of silica particles is likely to occur, resulting in low storage stability.

[0296] It has been confirmed through embodiments of the present invention that by using silica particles with Rsp values ​​that have a specific range as determined by pulse NMR in the silica sol used in the polishing composition, high polishing speeds can be obtained and storage stability can be improved when they are used as the polishing composition for polishing silicon wafers.

[0297] Therefore, the polishing composition of the present invention can be used not only as an polishing agent for polishing silicon wafers, but also as a polishing agent for CMP of device wafers due to its high polishing speed and storage stability.

[0298] Industrial availability

[0299] By using silica particles with specific Rsp values ​​obtained by pulsed NMR in the silica sol used in the polishing composition, a high polishing speed can be obtained when polishing silicon wafers, and the storage stability of the polishing composition can be improved.

Claims

1. A grinding composition comprising an aqueous dispersion of silica particles, wherein the Rsp value derived from the relaxation time of the aqueous dispersion of silica particles and pure water by pulse NMR measurement is 0.01 or higher and less than 0.

15. Rsp = (Rav - Rb) / (Rb) in, Rav is the reciprocal of the relaxation time of an aqueous dispersion of silica particles with a silica concentration of 5% by mass, and Rb is the reciprocal of the relaxation time of pure water. For silica particle powder obtained by freezing the treatment solution at a temperature of -70°C to -80°C and then freeze-drying it at room temperature under a pressure below 5 Pa to remove the dispersion medium, the silanol group content, calculated by the following formula using the mass loss when heated from room temperature to 700°C in thermogravimetric analysis and the molecular weight of water molecules, is 0.1~1.5 mmol / g. The treatment solution is obtained by sequentially contacting the aqueous dispersion of silica particles with a cation exchange resin, an anion exchange resin, and another cation exchange resin for ion exchange. The amount of silanol groups in mmol / g = 2 × (M2 - M1) ÷ M H2O ÷ (M0-M1)×1000 Where M0 represents the mass of silica powder used for the heating weight analysis before heating, M1 represents the mass reduction at the time point of reaching 200℃, and M2 represents the mass reduction at the time point of reaching 700℃. H2O This indicates the molecular weight of a water molecule.

2. The grinding composition according to claim 1, The average secondary particle size of the silica particles in the aqueous dispersion was determined by dynamic light scattering method to be 40~200nm, and the average primary particle size was determined by nitrogen adsorption method to be 20~100nm.

3. The grinding composition according to claim 1, The silica particle powder obtained by freezing the treatment liquid at a temperature of -70℃ to -80℃ and then freeze-drying it at room temperature under a pressure below 5 Pa to remove the dispersion medium had a density of 2.20~2.35 g / cm³, as determined by dry density measurement. 3 .

4. The grinding composition according to claim 1, For silica particle powder obtained by removing the dispersion medium by heating the treatment liquid at 140°C for 2 hours and then at 290°C for 1 hour, the specific surface area S based on the water vapor adsorption method is... H2O Compared to the specific surface area S based on nitrogen adsorption method N2 The ratio of S H2O / S N2 The value is 0.10~0.

65.

5. The grinding composition according to any one of claims 1 to 3, The silica particle aqueous dispersion is a dispersion that has undergone a thermal process at a temperature above 140°C and below 260°C.

6. The grinding composition according to any one of claims 1 to 4, The concentration of silica particles in the aqueous dispersion of silica particles is 1-40% by mass.

7. The grinding composition according to any one of claims 1 to 4, The grinding composition also contains at least one additive selected from acidic compounds, basic compounds, water-soluble compounds, chelating agents, oxidizing agents, and metal corrosion inhibitors.

8. The grinding composition according to claim 7, The alkaline compound is at least one alkaline compound selected from alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonates, and nitrogen-containing alkaline compounds.

9. The grinding composition according to claim 7, The chelating agent is an aminocarboxylic acid chelating agent or a phosphonic acid chelating agent.

10. The grinding composition according to any one of claims 1 to 4, The pH value of the grinding composition is 1~12.

11. The grinding composition according to any one of claims 1 to 4, In a test in which the grinding composition was heated and stored at 50°C for 28 days, the increase rate of the average secondary particle size of the grinding composition after being heated and stored at 50°C for 28 days, as determined by dynamic light scattering, was less than 5%, compared to the average secondary particle size of the grinding composition before being heated and stored at 50°C for 28 days.

12. The grinding composition according to any one of claims 1 to 4, The polishing composition is a composition used for polishing silicon wafers or device wafers.

13. A method for manufacturing a grinding composition, comprising: The process of preparing a colloidal silica dispersion as a precursor; and The process of obtaining the silica particle aqueous dispersion by heating the precursor at a temperature above 140°C and below 260°C.

14. A silica particle dispersion comprising a solvent and silica particles, wherein the Rsp value derived from the relaxation time of the silica particle dispersion and a blank solution by pulse NMR determination is 0.01 or higher and less than 0.

15. Rsp = (Rav - Rb) / (Rb) in, Rav is the reciprocal of the relaxation time of a silica particle dispersion with a silica concentration of 5% by mass, and Rb is the reciprocal of the relaxation time of the blank solution. For silica particle powder obtained by freezing the treatment solution at a temperature of -70°C to -80°C and then freeze-drying it at room temperature under a pressure below 5 Pa to remove the dispersion medium, the silanol group content, calculated by the following formula using the mass loss when heated from room temperature to 700°C in thermogravimetric analysis and the molecular weight of water molecules, is 0.1~1.5 mmol / g. The treatment solution is obtained by sequentially contacting the silica particle dispersion with a cation exchange resin, an anion exchange resin, and another cation exchange resin for ion exchange. The amount of silanol groups in mmol / g = 2 × (M2 - M1) ÷ M H2O ÷ (M0-M1)×1000 Where M0 represents the mass of silica powder used for the heating weight analysis before heating, M1 represents the mass reduction at the time point of reaching 200℃, and M2 represents the mass reduction at the time point of reaching 700℃. H2O This indicates the molecular weight of a water molecule.

15. The silica particle dispersion according to claim 14, The solvent contains water.

16. The silica particle dispersion according to claim 14, The average secondary particle size of the silica particles, as determined by dynamic light scattering, is 40-200 nm, and the average primary particle size, as determined by nitrogen adsorption, is 20-100 nm.

17. The silica particle dispersion according to claim 14, The silica particle powder obtained by freezing the treatment liquid at a temperature of -70℃ to -80℃ and then freeze-drying it at room temperature under a pressure below 5 Pa to remove the dispersion medium had a density of 2.20~2.35 g / cm³, as determined by dry density measurement. 3 .

18. The silica particle dispersion according to claim 14, For silica particle powder obtained by removing the dispersion medium by heating the treatment liquid at 140°C for 2 hours and then at 290°C for 1 hour, the specific surface area S based on the water vapor adsorption method is... H2O Compared to the specific surface area S based on nitrogen adsorption method N2 The ratio of S H2O / S N2 The value is 0.10~0.

65.

19. The silica particle dispersion according to any one of claims 14 to 18, The silica particle dispersion is a dispersion that has undergone a thermal process at a temperature above 140°C and below 260°C.

20. The silica particle dispersion according to any one of claims 14 to 18, The concentration of the silica particles is 1 to 40% by mass.

21. A method for manufacturing a silica particle dispersion, comprising: The process of preparing a colloidal silica dispersion as a precursor; and The process of obtaining the silica particle dispersion by heating the precursor at a temperature above 140°C and below 260°C.

Citation Information

Patent Citations

  • Polishing liquid, polishing method, semiconductor substrate and electronic apparatus

    JP2017117894A

  • Polishing composition and polishing method

    WO2015152151A1

  • Polishing composition, method for producing polishing composition, and polishing method

    WO2018012174A1

  • Polishing composition

    WO2018116890A1

  • Polishing composition using polishing particles that have high water affinity

    WO2020091000A1